Medio de comunicación digital la última y su influencia en la práctica de actividad física deportiva en los jóvenes del pital 1 en el cantón Quevedo - Intriago Chasiluiza, Jenniffer Estefanía (2018)
The present research project has as a priority the development of a program of sports activities in the digital medium The Last with the purpose that residents of the sector Pital 1 in the canton Quevedo, obtain and experience a lot of knowledge. In Ecuador, a law was established with the sole purpose of respecting rights, so that information is disseminated and access to different media is supported, such as print media, radio and television. The digital information media today are very useful for people because they help them to be communicated in an updated and fast way, allowing to obtain information of what happens in different parts of the world. Several methodologies were manipulated to elaborate the investigation. A questionnaire of questions was used, statistical graphs, these methods made feasible the study of relation of the variables to verify the effectiveness of the problem. It was finalized that the program of sports information in the digital medium is of great assistance for the residents of the sector the Pital 1, since they will be achieving much knowledge values and customs that will improve their life style.